Analysis of Gross Motor and Fine Motoric on Learning Outcomes of Physical Education at Public Elementary Schools (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
This research was conducted to analyze gross motor skills and fine motor skills with the learning outcomes of PJOK (Physical Education Sports Health) in Public Elementary School 1 Sumbergedong students. This type of research is a quantitative descriptive study. The population in this study were students at Public Elementary School 1 Sumbergedong Trenggalek. The sample in the study was taken by total sampling. The instrument used was a motor ability test (Motor Ability Test). The results showed that the male low class gross and fine motor skills were 48% and 40%, girls 79% and 52%, while the low class men’s learning outcomes were 39% and girls 51%. The male high-class gross motor skills were 38%, girls 49%, men’s fine motor skills 39%, girls 36%, while the high-class learning outcomes for boys were 77% and girls were 33%. Based on the research results, it can be concluded that students who have good motor skills tend to have good learning outcomes.